Confronted with Bullying when You Believe in a Just World - Voss, David; Newman, Leonard S. (Frontiers in Education, 2021)
Bullying has been recognized as a phenomenon that detrimentally affects the lives of many, and researchers continue to explore its various influences and correlates. We examined the relationship between the global belief in a just world (BJW; a person’s tendency to believe that life is fair and people get what they deserve) and reactions to bullying. Although BJW is undergirded by a justice motive, and although previous research found that global BJW is associated with more negative explicit attitudes toward bullying in the abstract, we hypothesized that strong global BJW beliefs would instead predict more tolerance and less condemnation when participants were presented with specific behaviors that could be construed as bullying. In two vignette-based experiments, global BJW (but not personal BJW), predicted less negative reactions to bullying, and did so regardless of whether the behavior was explicitly labeled as being a case of bullying. Implications of these results are discussed.